SPECIFIC ASPECTS OF THE ACTIVITY OF REPRESENTATIVES OF THE QADIRIYA SECT EXISTING TODAY (American Journal of Pedagogical and Educational Research, 2023)
This article analyzes the modern form and characteristics of Qadiriya sect, one of the global sects whose activities are being observed today.